Comparison of Chest X-Ray Assessment in Multi-Drug Resistance to Drug- Sensitive Tuberculosis Patients - Sari Afiah Miyuki Rifani; Zen Ahmad; M. Yusri; Erial Bahar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Introduction. Indonesia ranks third in tuberculosis cases, with 23,000 new dualdrug-resistant tuberculosis patients. The delay in predicting tuberculosis resistanceoccurs because sputum tools are not yet available. This study aimed to determinethe differences in chest x-rays for drug-sensitive multiple drug-resistanttuberculosis in Palembang. Method. A case-control design to compare theradiological characteristics of multiple drug resistance with drug-sensitive atPalembang during January-July 2020. One hundred thirty-eight patients consistedof cases of drug-sensitive tuberculosis and multidrug-resistant tuberculosis basedon the rapid molecular test that met the inclusion criteria, analyzed forposteroanterior chest X-rays by a radiologist without knowing the diagnosis—comparative chi-square using SPSS 22. Result. Multidrug resistance tuberculosishad more extensive or moderate lesions than drug-sensitive tuberculosis 89.8% vs72.4%. The multidrug-resistant group has more infiltrate detected, namely 84.1% vs69.6% and cavity 37.6% vs 30.4%. Atelectasis and pleural effusion are common indrug-resistant tuberculosis. Bivariate analysis showed that multidrug-resistanttuberculosis lesion infiltrates compared to drug-sensitive tuberculosis with p =0.025; OR 2,6 (CI 95% 1,1-6,0) sensitivity 85.5%, specificity 30.4%. Multivariateanalysis showed the presence of infiltrates p = 0.028; OR 2.58 (CI 95% 1.1-6.003).Consolidation, nodules, cavities, fibrosis, atelectasis, pleural effusion were notsignificant differences in the two groups. Conclusion. Multidrug-resistanttuberculosis has a more expansive lesion, the presence of infiltrates and cavities thatis more dominant than drug-sensitive tuberculosis.